Originally Posted by

**Soroban** Hello, Morzilla!

You did nothing wrong . . . just take another step.

we have: .$\displaystyle \sqrt{3x^2} + \underbrace{6\sqrt{108x^2} - 4\sqrt{108x^2}}$

. . . . . . . . $\displaystyle = \;\sqrt{3x^2} + 2\sqrt{108x^2}$

. . . . . . . . $\displaystyle = \;\sqrt{3x^2} + 2\sqrt{36\!\cdot3x^2}$

. . . . . . . . $\displaystyle = \;\sqrt{3x^2} + 2\!\cdot\!6\!\cdot\!\sqrt{3x^2} $

. . . . . . . . $\displaystyle = \;1\!\cdot\!\sqrt{3x^2} + 12\!\cdot\!\sqrt{3x^2}$

. . . . . . . . $\displaystyle = \;13\!\cdot\!\sqrt{3x^2}$ . . . . This is correct (so far)

. . . . . . . . $\displaystyle = \;13\!\cdot\!\sqrt{3}\!\cdot\!\sqrt{x^2}$

. . . . . . . . $\displaystyle = \;13\!\cdot\sqrt{3}\!\cdot\!x$

. . . . . . . . $\displaystyle = \;13x\sqrt{3}$